Comparison of two lung cancer screening scores among patients with chronic obstructive pulmonary disease: A community study. (21st February 2019) - Gagnat, Ane Aamli; Gulsvik, Amund; Bakke, Per; Gjerdevik, Miriam
Abstract: Introduction: Based on the National Lung Cancer Screening Trial (NLST), guidelines on screening programs for lung cancer have recommended low‐dose computed tomography (LDCT). De Torres et al made a score for COPD patients (COPD‐LUCSS) to improve their selection criteria. Objective: To examine and compare the discriminating value of both scores in a community‐based cohort of COPD patients. Methods: Four hundred and twenty‐two ever‐smokers with COPD from the GenKOLS study in Bergen were merged with the Cancer Registry of Norway. We divided the patients into groups of high and low risk according to the COPD‐LUCSS and the NLST criteria. Cox regression and logistic regression were used to analyse the associations between the scores and lung cancer. We used Harrell's C and area under the curve (AUC) to estimate discriminating values and to compare the models. Results: Hazard ratio for the high risk vs the low risk in the COPD‐LUCSS was 3.0 (1.4‐6.5 95% CI), P < 0.01. Hazard ratio for the NLST criteria was 2.2 (95% CI 1.1‐4.5), P < 0.05. Harrell's C was 0.63 for the COPD‐LUCSS and 0.59 for the NLST selection criteria. AUC was 0.61 for COPD‐LUCSS and 0.59 for NLST criteria. Comparing tests showed no differences ( P = 0.76). Conclusion: Although the COPD‐LUCSS and the NLST criteria were associated with increased risk of lung cancer, the AUC and Harrell's C values showed that these models have poor discriminating abilities in our cohort of COPD patients. The COPD‐LUCSS was not significantly better than the NLST criteria.